Three in One--Multiple Faunal Elements within an Endangered European Butterfly Species - Junker, Marius; Zimmermann, Marie; Ramos, Ana A; Gros, Patrick; Konvička, Martin; Nève, Gabriel; Rákosy, László; Tammaru, Toomas; Castilho, Rita; Schmitt, Thomas (PLoS One, 2015)
Ice ages within Europe forced many species to retreat to refugia, of which three major biogeographic basic types can be distinguished: "Mediterranean", "Continental" and "Alpine / Arctic" species. However, this classification often fails to explain the complex phylogeography of European species with a wide range of latitudinal and altitudinal distribution. Hence, we tested for the possibility that all three mentioned faunal elements are represented within one species. Our data was obtained by scoring 1,307 Euphydryas aurinia individuals (46 European locations) for 17 allozyme loci, and sequencing a subset of 492 individuals (21 sites) for a 626 base pairs COI fragment. Genetic diversity indices, F statistics, hierarchical analyses of molecular variance, individual-based clustering, and networks were used to explore the phylogeographic patterns. The COI fragment represented 18 haplotypes showing a strong geographic structure. All but one allozyme loci analysed were polymorphic with a mean FST of 0.20, supporting a pronounced among population structure. Interpretation of both genetic marker systems, using several analytical tools, calls for the recognition of twelve genetic groups. These analyses consistently distinguished different groups in Iberia (2), Italy, Provence, Alps (3), Slovenia, Carpathian Basin, the lowlands of West and Central Europe as well as Estonia, often with considerable additional substructures. The genetic data strongly support the hypothesis that E. aurinia survived the last glaciation in Mediterranean, extra-Mediterranean and perialpine refugia. It is thus a rare example of a model organism that combines attributes of faunal elements from all three of these sources. The observed differences between allozymes and mtDNA most likely result from recent introgression of mtDNA into nuclear allozyme groups. Our results indicate discrepancies with the morphologically-based subspecies models, underlining the need to revise the current taxonomy.
Keywords: genetická variace; Genetic Variation; motýli; Endangered Species; Animals; Phylogeny; Haplotypes; Phylogeography; DNA, Mitochondrial; Evropa; fylogeneze; fylogeografie; Europe; ohrožené druhy; mitochondriální DNA; Butterflies; haplotypy; zvířata